STRATEGI EDITOR DALAM MENINGKATKAN KREATIVITAS VISUAL PROGRAM FAKTA+62 DI MDTV - David Maulana (ADISAM PUBLISHER, 2025)
This study explores the editor's strategy in enhancing visual creativity in the Fakta+62 news program on the MDTV television station. In today's digital era, visual presentation in news broadcasts is not merely complementary but serves as a key element in capturing the audience's attention. The aim of this research is to identify and analyze the visual strategies applied by editors during the editing process and to understand how visual creativity strengthens news narratives. This research employs a descriptive qualitative method, using in-depth interviews with editors and program producers. The findings reveal that editors utilize various visual elements such as appropriate footage selection, dynamic transitions, informative graphics, and audio- visual synchronization to produce engaging and communicative news broadcasts. The study also highlights that time pressure, equipment limitations, and poor-quality footage are the main obstacles in the editing process. With well-planned visual strategies and creative input, editors are able to create news content that is not only informative but also aesthetically appealing